2010
DOI: 10.1007/s11060-010-0289-3
|View full text |Cite
|
Sign up to set email alerts
|

Low-level copy number changes of MYC genes have a prognostic impact in medulloblastoma

Abstract: High-level amplifications of MYC genes are associated with poor outcomes in childhood medulloblastoma (MB). However, the occurrence of MYCN and MYCC copy number increases below the intense amplification pattern is rarely reported, and its clinical impact has not yet been determined. Here, we describe this phenomenon and its prognostic significance in a cohort of 29 MB patients. Using interphase fluorescence in situ hybridization (I-FISH), low-level copy number alterations, i.e. gain of MYCN, were shown in 5/27… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 47 publications
1
15
1
1
Order By: Relevance
“…5%) within individual tumours highlights potential sampling limitations and the requirement for assessment of sufficient tumour nuclei ([200 in this study) to avoid false-negative results. Haploid copy numbers \5 were more commonly associated with chromosomal gains, which have been suggested elsewhere to confer a poor prognosis [4,28]; however, these did not show prognostic significance in multivariate survival analysis in the present study. Although significant in univariate survival analysis, the limited numbers of MYCN 'gained' cases (n = 2) dictate the requirement of extended studies to definitively assess their relationships to survival.…”
Section: Discussioncontrasting
confidence: 72%
See 3 more Smart Citations
“…5%) within individual tumours highlights potential sampling limitations and the requirement for assessment of sufficient tumour nuclei ([200 in this study) to avoid false-negative results. Haploid copy numbers \5 were more commonly associated with chromosomal gains, which have been suggested elsewhere to confer a poor prognosis [4,28]; however, these did not show prognostic significance in multivariate survival analysis in the present study. Although significant in univariate survival analysis, the limited numbers of MYCN 'gained' cases (n = 2) dictate the requirement of extended studies to definitively assess their relationships to survival.…”
Section: Discussioncontrasting
confidence: 72%
“…Studies by us and others have associated MYC family amplification with a poor prognosis; however, findings are not consistent between studies and suggest heterogeneous biological and clinical behaviour of the MYC genes [2,7,11,14,15,21,23,28]. Specifically, while some studies have combined MYCC and MYCN together for analysis and demonstrated prognostic significance [14,21], others have indicated their individual roles as prognostic biomarkers may differ; our most recent study found prognostic significance for MYCC but not MYCN [7].…”
Section: Introductionmentioning
confidence: 58%
See 2 more Smart Citations
“…Amplification of MYC family oncogenes appears to be pivotal for tumor biology and clinical behavior in up to 15% of pediatric cases [9,11,30,35,36]. It has been recognized that focal high-level amplification of the MYC (MYCC) locus at 8q24 was significantly associated with poor clinical outcome and this has been confirmed in various independent series [1,6,11,12,35,48].…”
Section: Introductionmentioning
confidence: 94%